Development of Creative Products for Strengthening the Community Economy through Products from Vetiver Grass Mixed Reed Fiber in Udon Thani Province - Kallayanee Kullachai; Peerachai Kullachai; Kokhanest Rungsanthia; Pasatorn Dechsiriudom (My University, 2023)
The purposes of this research were to 1) study the local wisdom of Khon Sai community in the production of reed products and exploring the capacity of production vetiver grass in Udon Thani province, 2) study for developing creative products made from vetiver grass leaves together with reeds, used of appropriate local natural dyes for manufacturing products in accordance with the market supply, and 3) assess the opinions on designed and developed products made of reed and vetiver grass leaves that can be used as a lesson learned for build a strong community in the future. The methodology of this study was a qualitative research method that consists of 4 steps: 1) collecting original local wisdom data by in-depth interviews and focus group discussions of 10 representatives from a community enterprise group, and by interviews of 30 consumers, 2) using the collected data to design and create a prototype, 3) evaluating products prototype by 2 experts and assessing the satisfaction on the prototype by 8 consumers 4) summarizing data analysis and synthesis. The results of this study found that there is the weaving of reed mats according to the local original wisdom in Khon Sai community. The most purchasing handicraft product by consumers was the mats (66.67 per cent) with the aim of utilizing in their families. The preferable product color of consumers was natural dyes. The researcher developed a handicraft products made from vetiver grass together with reeds, dyeing the natural color from vetiver roots and leaves. In this regard, it was used natural dyed reed and vetiver for weaving mats, and it was applied for designing and processing into 2 handbags prior to assessing such product by experts and consumers. According to evaluation, it was found that the product was beautiful, value-added, and applicable, resulting in a variety of products in the market and also reflects that reed and vetiver grass can be applied for maximum benefit and value addition creation in a concrete manner.
Keywords: Handicraft; Weaving; Strategic Planning and Analysis